DATA ON ANXIETY LEVEL OF DENTAL HOSPITAL UNIVERSITAS SUMATERA UTARA FIXED ORTHODONTICS PATIENTS IN NEW NORMAL: Anxiety level of Fixed Orthodontics Patients - Risfi (Indonesian Journal of Medical Anthropology, 2022)
The lockdown policy for certain dental care during pandemic COVID-19 could cause mental distress. This prolonged pandemic has frustrated orthodontists and patients before the emergence of vaccination. Since the initiation of COVID-19 mass vaccination in January 2021 by the Indonesian government, the aim of this study is to describe the anxiety level of patients undergoing fixed orthodontics treatment regarding routine care from February to May 2021. The highest anxiety level towards routine care during the COVID-19 pandemic was in moderate level (57.4%) and in severe level (40.7%). Both male and female patients showed moderate level of anxiety against routine care during the COVID-19 pandemic. Most patients who came for routine care are from late adolescence (17 to 25 years old) and with a bachelor degree. Orthodontists have to consider patients’ anxiety level in order to obtain a successful orthodontic treatment due to the previous temporary lockdown of the dental hospital. Since the definite time for the COVID-19 pandemic to end is still unknown, social intervention for patients should be considered in managing the mental distress that emerged. In this current time, the expansion of COVID-19 new variants has also become a dilemma for orthodontists and patients. The vaccination and routine screening for COVID-19 is advisable as the requirement for safe routine orthodontics control. Thus, education for oral health maintenance during orthodontics treatment will be an integral part of preventing the COVID-19 local transmission.